Fields-Garrison literary collection - Fields, James Thomas, 1817-1881.; Garrison, Wendell Phillips, 1840-1907.; Langel, August; Lowell, James Russell, 1819-1891.; Martineau, Harriet, 1802-1876.
Literary correspondence and manuscripts acquired by James Thomas Fields, editor of the Atlantic Monthly (1861-1870), and Wendell Phillips Garrison, editor of The Nation (1862-1906). Includes an typescript (in French) of August Langel's An American Diary (1864), abstract of James Russell Lowell's "Bigelow papers," and Harriet Martineau's book, Lights of the English Lake District. Correspondents include Charles Francis Adams, Henry Ward Beecher, Edwin Thomas Booth, Robert Browning, James Bryce, Jacob Dolson Cox, Ralph Waldo Emerson, John Fiske, Nathaniel Hawthorne, William Dean Howells, George Lyman Kittredge, Henry Wadsworth Longfellow, and Elizabeth Palmer Peabody.
Collection material in English, with French.
Keywords: Adams, Charles Francis, -- 1807-1886 -- Correspondence; Beecher, Henry Ward, -- 1813-1887 -- Correspondence; Booth, Edwin, -- 1833-1893 -- Correspondence; Browning, Robert, -- 1812-1889 -- Correspondence; Bryce, James Bryce, -- Viscount, -- 1838-1922 -- Correspondence; Cox, Jacob D. -- 1828-1900 -- Correspondence; Emerson, Ralph Waldo, -- 1803-1882 -- Correspondence; Fiske, John, -- 1842-1901 -- Correspondence; Godkin, Edwin Lawrence, -- 1831-1902.; Hawthorne, Nathaniel, -- 1804-1864 -- Correspondence; Howells, William Dean, -- 1837-1920 -- Correspondence; Kittredge, George Lyman, -- 1860-1941 -- Correspondence; Longfellow, Henry Wadsworth, -- 1807-1882 -- Correspondence; Peabody, Elizabeth Palmer, -- 1804-1894.; American literature